ANALISIS PERAN RELAWAN ORGANISASI AKU BELAJAR DALAM MENINGKATKAN MINAT BELAJAR ANAK PEMULUNG DI TPAS BATU LAYANG - Tiara Fahmiyatul Ulmi; Imran Imran; Iwan Ramadhan (Universitas Tanjungpura, 2021)
AbstrakThe purpose of this study was to determine the role of the Aku Belajar volunteer organization as a coach, motivator and facilitator in increasing the interest in learning of scavenger children at TPAS Batu Layang Pontianak Utara. The research approach used is a descriptive qualitative approach. The data collection techniques used were observation, interview and documentation. Data analysis techniques used data reduction, data presentation and drawing conclusions. The analysis in this research is presented descriptively. The results of this study indicate that the role of the Aku Belajar organization volunteers as guides, motivators and facilitators has been implemented. This is evidenced by the increasing interest in learning scavenger children. The increased interest in learning scavenger children is shown by the child through the attitude when learning, namely the feeling of pleasure seen in the child's joy while learning, the child's interest in learning can be seen when the child responds or responds to something while learning and the child's independence when doing assignments, the child's attention is seen if the child is serious and focus during the learning process. Children's involvement can be seen when children participate in AB activities. Then results and achievements were obtained both during AB activities and at school. This makes the assisted children feel proud and satisfied. However, there are still assisted children who cannot focus while studying due to internal and external factors. This is a challenge for AB volunteers.Keywords: Learning Interest, Role of Volunteers, Scavenger Children